A Comparison of the Effects of Fixed- and Rotating-Shift Schedules on Nursing Staff Attention Levels: A Randomized Trial. (October 2013) - Niu, Shu-Fen; Chu, Hsin; Chen, Chiung-Hua; Chung, Min-Huey; Chang, Yu-Shiun; Liao, Yuan-Mei; Chou, Kuei-Ru
Purpose: Sleep deficit affects neurobehavioral functioning, reduces attention and cognitive function, and negatively impacts occupational safety. This study investigated selective attention levels of nursing staff on different shifts. Methods: Using a prospective, randomized parallel group study, selective attention was measured using the d2 test in 62 nursing staff in a medical center in Taiwan. Findings: There were significant differences in selective attention indicators (E%) between the fixed-day-shift group (control group) and rotating-shift group (experimental group): The percentage of errors (E%) for night-shift workers in the rotating-shift group was higher than that of fixed-day-shift workers, while the total number of items scanned minus error (TN − E) and concentration performance (CP) scores were higher for fixed-day-shift workers. Within the experimental group, the error rate on night shift was 0.44 times more than that on day shift and .62 times more than on evening shift; the TN-E on night shift was 38.99 items less than that on day shift, and the CP was 27.68 items less on night shift than on day shift; indicating that staff on the night shift demonstrated poorer speed and accuracy on the overall test than did the staff on day shifts. Conclusions: Inadequate sleep and a state of somnolence adversely affected the attention and operation speed of work among night-shift workers. More than 2 days off is suggested when shifting from the night shift to other shifts to provide adequate time for circadian rhythms to adjust.